2015
DOI: 10.1111/ppa.12365
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny and origin of Fusarium oxysporum f. sp. vanillae in Indonesia

Abstract: Vanilla stem rot, caused by Fusarium oxysporum f. sp. vanillae (Fov), is the main constraint to increasing vanilla production in the major vanilla‐producing countries, including Indonesia. The current study investigated the origin of Fov in Indonesia using a multigene phylogenetic approach. Nineteen Fov isolates were selected to represent Indonesia, the Comoros, Mexico and Réunion Island. The translation elongation factor 1 alpha gene and the mitochondrial small subunit ribosomal RNA gene phylogenies resolved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
33
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 36 publications
3
33
1
1
Order By: Relevance
“…Only four isolates from Mexico, reported by Pinaria et al . (), were grouped in clade III, which is congruent with their results. However, another three isolates from Mexico (JAGH2, Nay18 and Nay20) belong to clade II, along with an Indonesian isolate (IndonesiaWN1).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Only four isolates from Mexico, reported by Pinaria et al . (), were grouped in clade III, which is congruent with their results. However, another three isolates from Mexico (JAGH2, Nay18 and Nay20) belong to clade II, along with an Indonesian isolate (IndonesiaWN1).…”
Section: Discussionsupporting
confidence: 89%
“…This is an important difference from the results of Pinaria et al . (), who reported that Mexican isolates were restricted to clade III; optimization of the pathogenicity trait shows that within this clade there are four different origins of the ability to infect vanilla.…”
Section: Discussionmentioning
confidence: 99%
“…The mtSSU gene was the least informative for differentiation of isolates of F. concentricum , F. mangiferae , and F. proliferatum . This accorded with the preferred use of the gene in classification among F. oxysporum , compared to other species of the genus (O’Donnell et al , ; Mbofung et al , ; Pinaria et al , ). In the present study, within F. oxysporum , there were only two clades (I and IV) of mtSSU tree and two clades (III and VII) of IGS tree but all clades (I–VII) of TEF1‐α tree were equivalent with the inclusion of isolates in either two or all clades generated from the combined gene sequences.…”
Section: Discussionmentioning
confidence: 90%
“…The mtSSU , IGS, and TEF1‐α are preferred genes for identification and phylogenetic classification of Fusarium species (O’Donnell et al , , ; Mbofung et al , ; Nitschke et al , ; Wang et al , ; Pinaria et al , ). In the present study, all three genes were informative in classifying the isolates of F. oxysporum , F. pseudocircinatum , and F. solani .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation